Inhibitory Effect of Azimilide on Na+/Ca2+ Exchange Current in Guinea-Pig Cardiac Myocytes - Yasuhide Watanabe; Junko Kimura (Elsevier, 2010)
We examined the effect of azimilide, a class III antiarrhythmic drug, on Na+/Ca2+ exchange current (INCX) in guinea-pig cardiac single ventricular cells. External application of azimilide suppressed bi-directional INCX in a concentration-dependent manner. IC50 values for outward and inward INCX were 45 and 40 μM, respectively, with Hill coefficients of 1. Azimilide attenuated INCX in the presence of trypsin in the patch pipette, indicating that azimilide is a trypsin-insensitive NCX inhibitor. Delayed afterdepolarization induced by electrical stimulation with ouabain disappeared in the presence of 30 μM azimilide. We conclude that azimilide inhibits NCX at supratherapeutic concentrations. Keywords:: antiarrhythmic drug, azimilide, Na+/Ca2+ exchange current (INCX)